PF-06409577 Activates AMPK Signaling and Inhibits Osteosarcoma Cell Growth - Zhu, Yun-Rong; Zhang, Xiang-Yang; Wu, Qiu-Ping; Yu, Cheng-Jian; Liu, Yuan-Yuan; Zhang, Yun-Qing (Frontiers in Oncology, 2021)
Osteosarcoma (OS) is a common primary bone malignancy. We here investigated the potential activity of PF-06409577, a novel, potent, and direct activator of AMP-activated protein kinase (AMPK), against human OS cells. In established (U2OS, MG-63, and SaOs-2 lines) and primary human OS cells, PF-06409577 inhibited cell viability and proliferation, while inducing cell apoptosis and cell cycle arrest. PF-06409577 induced AMPK activation, mTORC1 inhibition, autophagy induction, and downregulation of multiple receptor tyrosine kinase inOS cells. AMPK inactivation by AMPKα1 shRNA, CRISPR/Cas9 knockout, or dominant negative mutation (T172A) was able to abolish PF-06409577-induced activity in OS cells. In vivo, PF-06409577 oral administration at well-tolerated doses potently inhibited growth of U2OS cells and primary human OS cells in severe combined immunodeficient mice. AMPK activation, mTORC1 inhibition, autophagy induction, as well as RTK degradation and apoptosis activation were detected in PF-06409577-treated xenografts. In conclusion, activation of AMPK by PF-06409577 inhibits OS cell growth.